Degradation of Organic Matter and pH in Agricultural Soils by the Species of Zingiber Officinale R. (Ginger) within the Native Community the Milagro, Marankiari, Satipo, 2022 - Rios Aliaga, Jazmín (2024)
Soil degradation is caused by different types of crops in recent times, being one of the most relevant problems observed. Within the group of crops that are considered extractive is the species Zingiber Officinale r. (Ginger), since this species directly degrades the percentage of Organic Matter and the pH level. The development of this article aims to estimate the loss of chemical properties of the soil under cultivation of the species Zingiber Officinale r. (Ginger) within the Native Community the Milagro "Marankiari". For this study the following procedures were performed: preparation of a schedule, identification, and location of the area to be studied, survey of the land, collection of samples, drying, sieving, and packaging, finally, the samples were labelled and then sent to two different laboratories where the respective analysis was performed. The method used to develop this study was based on the search for information in the following journals: Scopus, ScienceDirect, etc. which reveal the direct influence of the species Zingiber officinale r. The results obtained in the analysis of the soil, shows that this crop reduced the percentage of organic matter 29.3% and increased the level of pH 0.1. It was seen that cultivating the species Zingiber officinale r. does degrade the organic matter and increase the pH of agricultural soils.